Kohesi Leksikal dalam Poster dan Iklan Layanan Masyarakat di Kota Pekalongan - Syifa, Siska Fala; Pramitasari, Afrinar (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study aims to describe the forms of lexical cohesion found in posters and public service advertisements in Pekalongan City. Lexical cohesion is an important element in building the integrity of discourse, especially in public messages that are short but still have to be effective and easy to understand. This research used descriptive qualitative method. Data were obtained through documentation, reading, and note-taking techniques on the discourse of posters and public service advertisements scattered in public spaces such as roads, terminals, places of worship, markets, and schools. The analysis shows that there is lexical cohesion consisting of: (1) collocation, (2) repetition which is used to emphasize the message and create memorability, (3) synonymy to maintain language variety and refine meaning, and (4) hyponymy which explains the meaning relationship between general and specific words. Collocation is the most dominant form of cohesion because it strengthens the relationship of meaning in the social context of the community. This finding confirms that lexical cohesion plays an important role in creating a cohesive, communicative, and persuasive public discourse, especially in delivering public service messages.